Heat transfer evaluation of turbulent flows through gear-ring elements - Ruengpayungsak, K.; Wongcharee, K.; Thianpong, C.; Pimsarn, M.; Chuwattanakul, V.; Eiamsa-ard, S. (My University, 2017)
Heat transfer and friction loss characteristics in tubular heat exchangers with gear-ring turbulators (GR-Ts) have been experimentally and numerically investigated. The GR-Ts with different free-space length ratios (SR = s/D = 1.0, 2.0 and 3.0) and tooth numbers (N = 8, 16 and 24), were experimentally tested under constant wall heat flux in turbulent flow (Reynolds numbers from 6000 to 20,000). Air was used as the working fluid. The behaviors in a plain tube and the tube with a conventional ring turbulators (N = 0) were also studied for comparison. The results show that utilizing tubes with GR-Ts leads to the increases of heat transfer coefficient and pressure loss as compared to those associated with the use of a plain tube. Heat transfer enhancement and friction increase with decreasing free-space length ratio (SR) and tooth number (N). Among the investigated inserts, the conventional ring turbulators (N = 0) with free-space length ratio, SR = 1.0 give the highest heat transfer rate and friction factor at 2.7 times and 15.5 times of those of the plain tube. However, the maximum thermal performance factor of 1.3 is obtained by using the GR-Ts with the largest free-space length ratio and maximum tooth number (SR = 3.0 and N = 24). At SR = 3.0, the GR-Ts with tooth numbers (N) of 0, 8, 16 and 24 yield thermal performance factors up to 1.24, 1.26, 1.28 and 1.3, respectively. The numerical results are given for a better understanding of flow and heat transfer characteristics associated with the use of GR-Ts.
Keywords: Gear-ring turbulator (GR-T); Heat transfer; Heat transfer enhancement; Ring turbulator; Turbulator